AKUMULASI STREPTOCOCCUS MUTANS PADA BASIS GIGI TIRUAN LEPASAN PLAT NILON TERMOPLASTIK DAN RESIN AKRILIK - Kadek Ayu Wirayuni (Faculty of Dentistry, Mahasaraswati Denpasar University, 2017)
Acrylic resin denture base are recently used as material for removable denture base, as well as thermoplastic nylon denture base that have flexibility and good esthetic. Both of these materials have porosity where food debris can attach and forming plaques. Plaque is the main habitat of oral microorganisms. One of the most frequent oral bacteria is Streptococcus mutans. Plaque and microorganism on denture could make an inflammation on soft tissue underneath the denture called denture stomatitis.The aim of this study was to understand the amount of Streptococcus mutans on thermoplastic nylon and heat cured acrylic resin removable denture base plate with 24 hours and 48 hours contact time.This study used 6 thermoplastic nylon plate and 6 heat cured acrylic resin square shaped with 10x10x1 mm size, and heat cured acrylic resin as control. Plates were soaked on tubes with Streptococcus mutans suspension at 24 hours and 48 hours contact time then all the objects were count. This study was an experimental laboratories and the method was randomized post-test only control group design federer. One Way Anova was used as the data analysis.The result shows statistically different of Streptococcus mutans amount on thermoplastic nylon and heat cured acrylic resin removable denture base plate with 24 hours and 48 hours contact time (p<0.05). Porosity of denture base may lead accumulation of Streptococcus mutans and contact time predispose bacterial growth. It is concluded that Streptococcus mutans amount on thermoplastic nylon removable denture base plate is less than heat cured acrylic resin and it is increase along with the contact time.